2014
DOI: 10.1007/s00221-014-4175-7
|View full text |Cite
|
Sign up to set email alerts
|

Improved gait adjustments after gait adaptability training are associated with reduced attentional demands in persons with stroke

Abstract: After stroke, the ability to make step adjustments during walking is reduced and requires more attention, which may cause problems during community walking. The C-Mill is an innovative treadmill augmented with visual context (e.g., obstacles and stepping targets), which was designed specifically to practice gait adaptability. The objective of this study was to determine whether C-Mill gait adaptability training can help to improve gait adjustments and associated attentional demands. Sixteen community-ambulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 45 publications
3
45
1
Order By: Relevance
“…C-Mill therapy is a structured treadmill training program with a specific emphasis on practicing walking adaptability (as detailed in Table 1 and Additional file 1), using gait-dependent augmented-reality content projected on the instrumented treadmill surface to elicit step adjustments [1, 1315, 2528]. Figure 3 shows various exercises of C-Mill therapy, including exercises to practice avoidance of projected visual obstacles (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…C-Mill therapy is a structured treadmill training program with a specific emphasis on practicing walking adaptability (as detailed in Table 1 and Additional file 1), using gait-dependent augmented-reality content projected on the instrumented treadmill surface to elicit step adjustments [1, 1315, 2528]. Figure 3 shows various exercises of C-Mill therapy, including exercises to practice avoidance of projected visual obstacles (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The secondary outcome measures are inspired by the targeted-stepping and obstacle-avoidance results of Hollands et al [35] and Van Ooijen et al [15], underscoring the importance of task-specificity and context-specificity in walking adaptability assessments. Van Ooijen et al [15] showed enhanced obstacle-avoidance success rates at lower attentional costs after a period of C-Mill walking adaptability therapy, while Hollands et al [35] showed that measures of targeted stepping were clinically meaningful components in the recovery of functional mobility after stroke.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations